Unpacking Paul's Wisdom: Applying Corinthian Solutions to Today's Church Dilemmas - Moses Adeleke Adeoye; Mordecai Gimba Suleiman; Theophilus Benjamin (Journal of Religious and Socio-Cultural, 2025)
Contemporary churches continue to wrestle with division, moral failures, spiritual elitism, and leadership scandals—struggles that mirror those faced by the first-century Corinthian church. This study examines how Paul’s instructions in 1 Corinthians offer enduring, practical wisdom for today’s ecclesial dilemmas. While much scholarship highlights Paul’s theology, fewer studies apply his counsel directly to modern crises such as church splits, abuse of spiritual gifts, or the collapse of trust in leaders. Using a qualitative historical-grammatical approach supported by biblical commentaries and concordances, this paper situates Paul’s message within its socio-cultural context and draws parallels for contemporary practice. The findings reveal four central contributions: unity in diversity as an antidote to factionalism, the equitable and orderly exercise of spiritual gifts, love as the supreme virtue for authentic community, and servant leadership as a safeguard against authoritarianism. These insights remain transferable across denominational lines and provide a framework for fostering healthier congregations. However, interpretive challenges persist, as modern contexts differ significantly from Corinth’s urban Greco-Roman world. Despite these limitations, Paul’s theology continues to speak powerfully into contexts of fragmentation and mistrust. This study contributes to scholarship by bridging the gap between Pauline exegesis and pastoral praxis, offering concrete, biblically grounded strategies for renewal in contemporary Christian communities.